Changes in tendon length and excursion following extensor tendon grafting at the distal radioulnar joint. (September 2022) - Hashimoto, Shun; Kato, Hiroyuki; Uchiyama, Shigeharu; Itsubo, Toshiro; Matsuda, Satoshi; Hayashi, Masanori
We evaluated the tendon length and excursion after extensor tendon grafting following ruptures at the distal radioulnar joint in eight patients. The mean patient age was 70.8 years (range 58 to 84), and the mean follow-up period was 63 months (range 12 to 129). Radiographic markers were placed on ends of the grafted tendon to assess changes in length and passive excursion. The mean length of the grafted tendon and mean passive excursion were 68.2 mm and 4.4 mm immediately after tendon grafting, 76.1 mm and 7.1 mm at 1 year postoperatively, and 76.3 mm and 7.3 mm at final follow-up, respectively. The mean elongation of the grafted tendon was 12% and mean increase of excursion was 2.9 mm. We recommend that tension set during extensor tendon grafting should be with the metacarpophalangeal joint of the affected finger in a slightly extended position as compared with adjacent fingers. Level of evidence: IV